Distributed-Relay Beamforming for Secrecy Energy Efficiency With Coordinated Eavesdroppers - Ouyang, Jian; Lin, Min; Zhu, Wei-Ping; Hong, Tao; Xu, Ba (IEEE communications letters, 2018)
This letter proposes a secure and energy efficient beamforming scheme for a distributed amplify-and-forward relay network against multiple coordinated eavesdroppers. Specifically, an optimization problem is formulated to maximize the secrecy energy efficiency (SEE), defined as the ratio of secrecy rate (SR) to total power consumption, subject to the target SR and both total and individual relay transmit power constraints. Due to the difficulty in solving this problem arisen from the non-convexity of fractional form of SEE and logarithmic subtraction of SR, we first adopt the Dinkelbach's method to handle the original problem by iteratively solving a sequence of parametric problems. Then, by jointly applying the penalty function approach and the difference of convex functions programming, we convert the parametric problem into a convex one which can be further approximated as a second order cone programming problem to reduce the computational complexity. Finally, we propose an iterative algorithm to find the near-optimal solution. Numerical results demonstrating the effectiveness of the proposed scheme and its advantage over the conventional approaches are provided.